HUBUNGAN ANTARABANGSA: TEORI DAN PRAKTIS (INTERNATIONAL RELATIONS: THEORY AND PRACTICE; A REVIEW - Makmor Tumin (Universitas Nasional, 2023)
Roy Anthony Rogers, Tunku Mohar Mokhtar and Wan Sharina Ramlah Wan Ahmad Amin Jaffri's book